Józef Święcicki (1859-1913) - architekt przypomniany i doceniony (Kronika Bydgoska, 2013)
Józef Stanisław Święcicki was born in Bydgoszcz on March 9, 1859. He was the son of shoemaking master Franciszek and Michalina nee Wojtalewicz. From the age of six he remained in the care of his stepfather, masonry master Anton Hoffmann, and this fact determined his future. In the years 1875-1880, having completed a community school, he continued his education at a basic vocational school of construction, most probably in Dresden, and completed it with a state examination entitling him to use the title of construction master.In the years 1881-1884, with Hoffmann he had a family design-contracting firm, and starting from 1885 he operated on his own. He designed over 50 tenement houses and detached villas, as well as over 100 smaller building structures, the monumental ”Pod Orłem” Hotel and a now non-existent summer theatre, which were constructed in Bydgoszcz in the years 1882-1905. He also designed two tenement houses in Inowrocław and one in Solec Kujawski. In his designs he used historicism, mainly Neo-Baroque and Neo-Renaissance styles.He was a keen chess player, social activist, philanthropist, dramatist, author of a guidebook around Bydgoszcz, and co-author of a professional dissertation on timber mould. In 1903, he officially changed the spelling of his surname to ”Swensitzky”. He died in Berlin on November 2, 1913 due to an unfortunate accident. The place of his final rest is the Nowofarny Cemetery in Artyleryjska Street in Bydgoszcz. He left his wife, Maria Henrietta nee Ehrlich and adopted son, Hugon Rudolf.From June 2008 to May 2009, Bydgoszcz celebrated the Year of Józef Święcicki. At that time, the viaduct in Gdańska Street was named after him, and a plaque commemorating him was placed on the tenement house in 63 Gdańska Street, which he constructed and where he lived periodically.